Activation by zinc of the human gastrin gene promoter in colon cancer cells in vitro and in vivo1. Issue 10 (7th October 2015) - Marshall, Kathryn M.; Laval, Marie; Estacio, Ortis; Hudson, Damien F.; Kalitsis, Paul; Shulkes, Arthur; Baldwin, Graham S.; Patel, Oneel
<x xml:space="preserve">Abstract</x> Over-expression of growth factors can contribute to the development and progression of cancer, and gastrins in particular have been implicated in accelerating the development of gastrointestinal cancers.